Humanitarianism in the Modern World The Moral Economy of Famine Relief - Götz, Norbert (Social Sciences, 2020)
Takes a fresh look at the history of famine relief and humanitarianism through a novel moral economy approach, drawing on case studies of the Great Irish Famine in the 1840s, the famine in Soviet Russia in 1921-3, and the famine in Ethiopia in the mid-1980s. This book is also available as Open Access on Cambridge Core.